2022
DOI: 10.1002/solr.202101007
|View full text |Cite
|
Sign up to set email alerts
|

Review of Two‐Step Method for Lead Halide Perovskite Solar Cells

Abstract: The quality of the perovskite film is crucial to the technological breakthrough of perovskite solar cells (PSCs). The two‐step method can facilitate the formation of a perovskite film with high quality and reproducibility. Many milestones have been made in the development of hybrid lead halide PSCs by using the two‐step method, which has a significant impact on their practical application. Herein, the reaction mechanism of the two‐step method including two‐step immersion method and two‐step spin coating method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 205 publications
1
65
0
Order By: Relevance
“…In terms of perovskite film formation by a two-step solution reaction, a porous lead halide film with a flat surface makes the reaction occur more easily and leads to the formation of a pure-phase and compact film. 40,41 Therefore, we speculate that the 0.10 M CsCl additive seems to be the best choice for preparing the target sample. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of perovskite film formation by a two-step solution reaction, a porous lead halide film with a flat surface makes the reaction occur more easily and leads to the formation of a pure-phase and compact film. 40,41 Therefore, we speculate that the 0.10 M CsCl additive seems to be the best choice for preparing the target sample. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, a spun‐cast lead iodide (PbI 2 ) layer was prepared first, followed by the thermally diffused organic salt ions. [ 28 ] We found that the formation of an incomplete perovskite phase during the crystal growth process after annealing leaves an unreacted PbI 2 component that causes low crystallinity, pinholes, and irregular grains in the resulting perovskite film, eventually negatively affects optoelectronic properties, i.e., electronic disorders and/or a shunt device. Figure 1c shows a top‐view SEM image of the spun‐cast PbI 2 –CsI layer.…”
Section: Resultsmentioning
confidence: 99%
“…However, bulk perovskites are unstable under ambient atmosphere and irradiation, which triggers studies on their more stable reduceddimensional counterparts, namely 0D quantum dots, 2D, and quasi-2D. Comprehensive reviews on the synthesis of perovskites can be found in [5][6][7][8][9]62,63], and therefore we summarize the synthesis methods of perovskites with different dimensions for optoelectronic applications in this review.…”
Section: Synthesis Of Lead Halide Perovskitesmentioning
confidence: 99%
“…Alternatively, the organic salt solution is spin-coated on the inorganic layer to form the desired 3D LHPs (Figure 3a). For the two-step sequential deposition methods, it is important to control parameters to obtain the high-quality film, such as the morphology of the inorganic layer at the first step, the concentration of the organic salt solution, and the speed of the spincoating [62]. Although the two-step method offers good reproducibility and compact films, it often encounters an issue of incomplete conversion.…”
Section: D Lead Halide Perovskitesmentioning
confidence: 99%